The conceptual evolution of Maqāṣid al-Syarī'ah: A historical study of the transformation of major principles in Islamic thought - Firmansyah Firmansyah; Zul Ikromi; Hellen Lastfitriani (Priviet Social Sciences Journal, 2026)
This study examines the conceptual evolution of maqāṣid al-syarī'ah by tracing the transformation of its main principles in the historical trajectory of Islamic thought. The main problem raised is the lack of comprehensive integration of historical analysis in tracing changes in the epistemological and methodological structure of maqasid from the classical to contemporary eras. The problem in this study is the approach of Maqashid with Hikmah, 'Illat, then its urgency and history. The purpose of this study is to find out the history and development of maqashid. The method used is qualitative research based on literature studies, with a historical-philosophical approach that examines the works of classical scholars. The conclusion of this study is that the relationship between wisdom, 'illat and maqashid is to solve the benefits of sharia law in the matter of ijtihad, then the urgency of maqashid is to maintain religion, soul, intellect, descendants, property, and honor. The history of its development has been carried out by the ijtihad of the prophet Muhammad PBUH and there have been phases of ups and downs.